Estudio entomatológico y transmisión de la verruga en el departamento de Ancas - Neyra Ramirez, Jose (1973)
The aunthors have studied the epidemiology of Bartonellosis (Carrión's disease) in Ancash, Perú. The Work strated in Casma and was carried out until hullanca across Huaraz covering a total distance of 395 Kms. During this traveling survery we observe the topography of the country, house resources and the characteristics of the human population of the region.  Phelebotomus peruensis was found in two places. We did not find Phlebotomus verrucarum. Tha analisis of the medical statistics of the hospitals of Huaraz, since 1958 until 1972, show that bartonellosis still is an endemic disease in the province of Ancash with tendency to declinate and predominance of the cutaneous type (Verruga peruana) of the disease.